Developing Mall-Based Reading Comprehension Test for Seventh Grade by Using Quizizz - Yunita Ayu Riski; Sri Wahyuni (Universitas Galuh, 2023)
This study aims at developing reading comprehension test based on Mobile Assisted Language Learning (MALL) for seventh grade of Junior High School students. It is adapted R and D development model proposed by Borg and Gall consisting of seven steps: research and information collection, developing a preliminary product, expert validation, product revision, field-testing/try-out, revision, and final product. On the basis of preliminary research and information collections result, the preliminary product was produced by considering MALL concept with Quizizz application. From the expert validation, it shows that the developed reading comprehension test in Quizizz was on good criteria and appropriate for seventh grade students, she suggested to provide clear picture related to the question, discard or replace unfamiliar song questions because it will make students confused in understanding the context. Next, the instructions were needed to be revised to be clearer and simple. The researcher tried out the test for 20 students in the seventh grade. The result of the try-out shows that there are 20 multiple choices test, but 18 test are valid because the significant value is more than 0.05 with rtable 0.422. The test has a level of difficulty from medium to easy as evidenced by the mean items difficulty of 0.25 to 0.85. It is also reliable with the significance value 0.934. With MALL-based reading comprehension test using Quizizz, students are more interested and enthusiastic in reading English questions. For them, the test is unique like playing an online game.